NewConnect as an Alternative Trading System - Schweda, Magdalena (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
The present paper is focused on NewConnect that is a new market that was organized and has been operated by the Warsaw Stock Exchange next to the main regulated market. On 30 August 2009 this new trading platform celebrated the second anniversary of its functioning. Because of a short period of its operation, NewConnect still remains unknown and mysterious for both potential issuers and investors as well as for many individuals interested in stock exchanges and capital markets. This common unfamiliarity with the NC Market operations is an essential obstacle to its development whereas NewConnect has a chance to become a significant part of the Polish capital market. It is intended for young dynamic Polish and foreign entities as an alternative source of capital required for financing of small and very innovative companies and investments. It gives them a chance to raise capital at a lower cost. On the other hand, investors gain a great opportunity to become shareholders in a company with the prospects of success. The aim of this paper is to present basic information about the NC Market, its rules, participants as well as to provide some statistics of NewConnect functioning from its beginning in August 2007 until the end of August 2009.